2007
DOI: 10.1124/dmd.106.013490
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Interleukin-10 with Mannose 6-Phosphate Groups Yields a Liver-Selective Cytokine

Abstract: ABSTRACT:Cytokines are considered a promising immunotherapy for chronic diseases, because of their potency and fundamental roles in pathological processes. However, their therapeutic use is limited because of their poor pharmacokinetics and pleiotropic effects in various organs. These problems may be overcome by cell-specific delivery of the cytokine. This approach involves chemical modification of the protein with homing devices that recognize receptors on target cells. The cytokine interleukin-10 (IL10) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Mannose 6-phosphate (M6P)-modified nanoparticles, such as M6P-HSA (or M6P-HSA-liposome), and N-(2-hydroxypropyl) methacrylamide, which contains M6P and tetrapeptide (GFLG), have been used to target stellate cells (Adrian et al, 2007;Beljaars et al, 2001;Li et al, 2009;van Beuge et al, 2011van Beuge et al, , 2013Yang et al, 2009). However, they are also taken up by Kupffer cells and LSECs because M6P-modified delivery systems can accumulate on the scavenger receptors expressed on these cells (Rachmawati et al, 2007). Administration of polyinosinic acid, an inhibitor of scavenger receptors, was found to inhibit the accumulation of M6P-modified nanoparticles in Kupffer cells and LSECs, but not in stellate cells (Adrian et al, 2007), because stellate cells take up M6P-modified nanoparticles through mannose-6-phosphate/insulin-like growth factor II, receptor-mediated endocytosis (Rachmawati et al, 2007).…”
Section: Use Of Liver Cell-targeted Delivery Systems For Treating Hepmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannose 6-phosphate (M6P)-modified nanoparticles, such as M6P-HSA (or M6P-HSA-liposome), and N-(2-hydroxypropyl) methacrylamide, which contains M6P and tetrapeptide (GFLG), have been used to target stellate cells (Adrian et al, 2007;Beljaars et al, 2001;Li et al, 2009;van Beuge et al, 2011van Beuge et al, , 2013Yang et al, 2009). However, they are also taken up by Kupffer cells and LSECs because M6P-modified delivery systems can accumulate on the scavenger receptors expressed on these cells (Rachmawati et al, 2007). Administration of polyinosinic acid, an inhibitor of scavenger receptors, was found to inhibit the accumulation of M6P-modified nanoparticles in Kupffer cells and LSECs, but not in stellate cells (Adrian et al, 2007), because stellate cells take up M6P-modified nanoparticles through mannose-6-phosphate/insulin-like growth factor II, receptor-mediated endocytosis (Rachmawati et al, 2007).…”
Section: Use Of Liver Cell-targeted Delivery Systems For Treating Hepmentioning
confidence: 99%
“…However, they are also taken up by Kupffer cells and LSECs because M6P-modified delivery systems can accumulate on the scavenger receptors expressed on these cells (Rachmawati et al, 2007). Administration of polyinosinic acid, an inhibitor of scavenger receptors, was found to inhibit the accumulation of M6P-modified nanoparticles in Kupffer cells and LSECs, but not in stellate cells (Adrian et al, 2007), because stellate cells take up M6P-modified nanoparticles through mannose-6-phosphate/insulin-like growth factor II, receptor-mediated endocytosis (Rachmawati et al, 2007). Interestingly, HSA terminated with 28 M6P [M6P(28)-HSA] strongly binds to activated stellate cells, but not to quiescent stellate cells (Beljaars et al, 2001).…”
Section: Use Of Liver Cell-targeted Delivery Systems For Treating Hepmentioning
confidence: 99%
“…Other proposed approaches to target specific tissues are the use of fusion proteins of IL-10 and monoclonal antibodies specific for the targeted cell type, that has been shown to be effective in an experimental model of rheumatoid arthritis [48], and the chemical alteration of IL-10. IL-10 modified with mannose-6 phosphate shows a prevalent homing to the liver, in particular to fibrogenic hepatic stellate cells expressing the mannose 6 phosphate/insulin-like growth factor II receptor, and could be applied to the treatment of cirrhosis [49]. The safety of some of these approaches is still in question, but they hold the promise to allow the targeted deliver of IL-10 into specific tissues or cell types and/or a regulated IL-10 production by the patient, thus reducing the systemic impact of the therapy.…”
Section: Il-10 and Il-10 Agonistsmentioning
confidence: 99%
“…Both in vitro and in vivo studies in male Wistar rats showed that these NPs were a potent nanocarrier for targeting HSC and can utilize the immune response against fibrosis. [63][64][65] A similar kind of study was done by another group using M6P to modify HSA, which showed successful delivery of DOX, cisplatin and chlorambucil for the pharmacotherapy of liver fibrosis. The reduction in liver fibrosis markers was confirmed using in vitro studies as well as in vivo studies in BDL rats.…”
Section: Other Npsmentioning
confidence: 99%